Seroprevalence and associated risk factors for Hepatitis B Virus infections among apparently healthy pregnant mothers attending Anc in Rubkona primary health care center in Rubkona County, Unity State, South Sudan - Michael Pou Machar; Dube Jara (Archives of Hepatitis Research - Peertechz Publications, 2021)
Background: Hepatitis B is an infection caused by the Hepatitis B Virus (HBV), which is enveloped DNA virus that infects the liver, and the common complications are; cirrhosis, liver cancer and rest of organs failure. Methods: A cross sectional study was conducted among 234 pregnant women attending antenatal Clinic in Rubkona primary Health care center in Rubkona County, South Sudan from March 1 to July 29. Data were collected using pretested interviewer administered questionnaire. Blood was withdrawn from each study participants and used to detect hepatitis B surface Antigen using an enzyme linked immune-sorbent assay test kit. Bivariate logistic regression was carried out to identify the predictors associated with HBV infection. All variables with p-value of ≤ 0.25 in bivariate logistic regression were taken into multivariable model. Variables having p value ≤ 0.05 in the multivariate analysis were taken as significant predictors.  Objectives: To assess the sero-prevalence Hepatitis B surface antigen and its associated factors among pregnant women attending Rubkona Primary Health Care Centre (South Sudan).  Result: The overall Sero-prevalence of HBV infection was, 16 (6.8%), 95% CI; 3.8-10.3). Having history jaundice AOR= 10.91:95%CI (2.6-45.2)], abortion history, [AOR= 5.5: 95%CI (1.5-23.5)] and history multiple sexual partner [(AOR= 9.5:95%CI (2.3-39.7)]. Were found to be associated factors of sero-prevalence of HBV infection. Conclusion: Hepatitis B is identified to be a major health problem in this community. According to WHO classification, the prevalence of HBV infection in this study area can be categorized as moderate prevalence (2-7%). Abortion and history multiple sexual partners found to be the risk factor associated with HBV infection.